2016
DOI: 10.1039/c5ra16469a
|View full text |Cite
|
Sign up to set email alerts
|

Using a biomimetic membrane surface experiment to investigate the activity of the magnetite biomineralisation protein Mms6

Abstract: Using a surface-based mimic of a magnetosome interior, the biomineralisation protein Mms6 was found to be a more effective nucleator than binder of magnetite nanoparticles, and performs better than its C-terminal region alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
48
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 34 publications
(50 citation statements)
references
References 35 publications
2
48
0
Order By: Relevance
“…In contrast, FliC‐Mms6_C subunits were not able to interact with the magnetite surface. These results are consistent with a recent study that suggested that Mms6 binds to iron ions (especially ferrous) rather than to magnetite surfaces . The same study found that the full protein—not just the C‐terminal section—is required for the iron‐binding property of Mms6.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In contrast, FliC‐Mms6_C subunits were not able to interact with the magnetite surface. These results are consistent with a recent study that suggested that Mms6 binds to iron ions (especially ferrous) rather than to magnetite surfaces . The same study found that the full protein—not just the C‐terminal section—is required for the iron‐binding property of Mms6.…”
Section: Discussionsupporting
confidence: 92%
“…Recently it was demonstrated that Mms6 binds to ferric and ferrous ions rather than to magnetite surfaces, and is a nucleating agent rather than a controller of magnetite crystal growth . Mms6 attached to surfaces has been used for the patterned formation of magnetite . In our experiments, the loop region of MamI and the 25‐residue C‐terminal region of Mms6 were inserted into flagellin in place of the D3 domain.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…Due to its amphiphilic sequence, purified Mms6 self‐assembles into micellar structures . These large aggregates are able to both bind and accumulate ferric ions from solution, and purified assemblies of Mms6 on a biomimetic magnetosome interior surface demonstrate magnetite formation properties, indicating that Mms6 can act as a potential iron oxide nucleation site for subsequent crystal formation . In addition, the acid rich C‐terminal part of Mms6 has been studied and was found to exhibit some similar characteristics to the full‐length protein such as iron binding and a limited ability to affect magnetite crystal growth …”
Section: Introductionmentioning
confidence: 99%
“…In their very recent study, they have used a similar biomimetic system to investigate the differences between the Mms6 C-terminal peptide and the intact Mms6 protein in magnetite synthesis. [298] …”
Section: Protein Mediated Synthesis Of Magnetite Nanoparticlesmentioning
confidence: 99%